A time to woo - Langton, Patti (Bristol : BBC Education and Training)
Story about social life and customs of Ait Hadiddu people in Morocco.
Film editor, Sue Outlaw ; series editor, Alan Bookbinder
Keywords: Ethnology -- Morocco; Moroccans -- Marriage customs and rites